The effect of application of organic matter during planting on growth of an East African highland cooking banana grown on two contrasting soils in south Kivu, eastern DR-Congo - Ntamwira, J.; Nzawele, D.B.; Katunga, D.; Asten, Piet J.A. van; Blomme, Guy (2010)
Highland bananas grown near the homestead in Eastern Democratic Republic of Congo receive organic household residues and are often mulched. Farmers also tend to allocate their best land for banana cultivation. However, due to an increased demand for bananas, farmers have started establishing banana plots on less fertile land. An experiment was conducted to assess plant growth on plots further away from the homestead and with minimal amounts of organic matter input. Two sites with .....